MANAJEMEN KOMUNIKASI PENERAPAN APLIKASI MONICA PADA PENYALURAN SUBSIDI TEPAT SASARAN LPG 3 KG DI KOTA PALEMBANG (STUDI KASUS PT RIZQI PUTRA ADIL GEMILANG) - Effendy, Saladdin Wirawan (Prospect Publishing, 2024)
This study aims to describe communication management activities in the policy implementation of the Monica application for the targeted distribution of 3 kg LPG subsidies in Palembang City. The research method used is qualitative, employing in-depth interviews and observations of research objects consisting of base respondents, consumer communities, and agents, followed by drawing specific messages or conclusions. The results show that the communication management required to ensure the implementation of this policy involves several cycles of management principles, so the Monica application policy can be fully applied in the targeted distribution of 3 kg LPG subsidies. The implication of this communication management is the successful achievement of the government's policy objectives in applying targeted 3 kg LPG subsidies to the community. Keywords: management, communication